2018
DOI: 10.4012/dmj.2017-328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silicate-based composite material on the proliferation and mineralization behaviors of human dental pulp cells: An <i>in vitro</i> assessment

Abstract: The objective of this study was to investigate the effects of a silicate-based composite material on proliferation and mineralization of human dental pulp cells (hDPCs), which was compared with those of calcium hydroxide (Ca(OH), CH) and tricalcium silicate (CaSiO, C3S). HDPCs were cultured with CH, C3S and tricalcium silicate/dicalcium silicate (CaSiO/CaSiO, C3S/C2S) composites extract. The CCK-8 assay showed that the composite material stimulated the proliferation of hDPCs. The odontogenic marker genes and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In addition, Shie et al 47) found that compared to silicates with a lower silicon content, silicates with a higher silicon content could promote cell adhesion, proliferation and differentiation to osteoblasts, which suggests that it is important to pay attention to the silicon content when designing pulp-capping agents. In our previous study 48) , a silicate-based composite material with Si/Ca molar ratios of 1:3 and 1:2 also promoted mineralization compared to CH.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, Shie et al 47) found that compared to silicates with a lower silicon content, silicates with a higher silicon content could promote cell adhesion, proliferation and differentiation to osteoblasts, which suggests that it is important to pay attention to the silicon content when designing pulp-capping agents. In our previous study 48) , a silicate-based composite material with Si/Ca molar ratios of 1:3 and 1:2 also promoted mineralization compared to CH.…”
Section: Discussionmentioning
confidence: 79%
“…Although this seems to be counterintuitive, it is possible that the high alkalinity of the calcium silicate‐based sealer media can up‐regulate alkaline phosphatase activity and enhance mineralization (Wu et al . 2018). Moreover, the main component of both calcium silicate‐based sealers is calcium silicates, whose mineralization capacity has previously been reported (Zordan‐Bronzel et al .…”
Section: Discussionmentioning
confidence: 99%
“…We chose this cell type because, in the indications of these materials, PDLSCs have contact with the periodontal ligament which are at the root-end cavity when periapical surgery is done or when iatrogenic perforation is repaired it is next to the periodontal ligament [10,21]. Other studies have used dental pulp stem cells with direct pulp capping materials [22], or osteoblast cells when they have also studied endodontic cements [23,24]. Therefore, the clinical situation is crucial for the choice of cell line.…”
Section: Discussionmentioning
confidence: 99%